PENAFSIRAN LAFADZ IHSAN DALAM AYAT-AYAT BIRRUL WALIDAIN: (STUDY LIVING QUR’AN SANTRIWATI KELAS XI MA DI PONDOK PESANTREN MODERN ISLAM ASSALAAM 2023) - Oktaviani, Rizka Dwi; Azizah, Alfiyatul (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2023)
The implementation of understanding the verses of the Qur'an by society is very diverse, both within the scope of large communities and miniature communities such as Islamic boarding schools. Like wise with the phenomenon of life at the Assalaam Islamic Modern Islamic Boarding School. Like the problems of other middle class families, the students of the Assalaam Surakarta Islamic Modern Islamic Boarding School have problems regarding the relationship between children and parents. Even though Islamic boarding schools in this case have instilled good values in family relationship patterns, in reality there are not a few differences among students in their implementation. This research aims to determine the understanding and implementation of class Student students in class This research is qualitative with an interpretive approach and uses descriptive analytical interpretive as a data analysis method. Based on the data, this research focuses on understanding the meaning, sources of knowledge and implementation of ihsan in the Birrul Walidain verses for female students in class on the verse and its implementation. In this case, environmental factors and scientific level are one of the most influential factors for students in realizing the values understood from the verses of the Al-Qur'an.